If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2t + 2) + -9 = 2 Reorder the terms: 4(2 + 2t) + -9 = 2 (2 * 4 + 2t * 4) + -9 = 2 (8 + 8t) + -9 = 2 Reorder the terms: 8 + -9 + 8t = 2 Combine like terms: 8 + -9 = -1 -1 + 8t = 2 Solving -1 + 8t = 2 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 8t = 2 + 1 Combine like terms: -1 + 1 = 0 0 + 8t = 2 + 1 8t = 2 + 1 Combine like terms: 2 + 1 = 3 8t = 3 Divide each side by '8'. t = 0.375 Simplifying t = 0.375
| 19x-5=13x-35 | | p-18=-29 | | 6-6x=-3x-6 | | x+.75=2x-.75 | | 0.333333333x+y=4 | | 2r+8/4=3r-9/3 | | x+x+40=90 | | 1/4[4-x]=10+2x | | -1=41+x/3 | | 5x+7(9x+8)= | | 2x-3(x-4)=2(3-2x)+2 | | 7p^2+65p+18=0 | | 6+y=12 | | 5x-6+2x=8 | | 5x=7(9x+8) | | -1.89+7.14=m | | 4m+12=-32 | | -24-12.5p=37.5p | | 3x+1=1200000 | | 5x+10+4x=-53 | | x-(-5.60)=4.5 | | 9x-x= | | 2.5x=2(x+5) | | x-(-23)=35 | | 7x^2+47x+30=0 | | -7=6n-1 | | 2(n-2)=4 | | 7w+w= | | -2+x+5x=46 | | 7(3k-2)+5=6(2k-1)+24 | | 7y+3=6y-6 | | 6=-2(7-6) |